Nickel-based electrode with high corrosion resistance and strong gassing performance and preparation method thereof

By acid treatment and plasma nitrogen doping treatment on the aluminum nickel alloy coated nickel mesh, a nitrogen-doped aluminum nickel alloy electrode with high corrosion resistance and strong gas analysis was prepared, which solved the problems of high overpotential and insufficient chlorine corrosion resistance in the prior art in the alkaline environment, and achieved efficient alkaline seawater electrolysis.

CN119753720AActive Publication Date: 2025-04-04HAINAN UNIV +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411597486.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-04-04
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

In the prior art, it is difficult to develop efficient, low-cost, non-precious metal electrocatalysts in alkaline seawater electrolysis, and nickel-based alloys have high overpotentials in alkaline environments and lack chlorine corrosion resistance.

Method used

Aluminum-nickel alloy coated nickel mesh was used as the precursor material, and after acid treatment and plasma treatment, a supported nitrogen-doped aluminum-nickel alloy electrode was prepared. The process includes soaking in an acid solution at room temperature, removing impurities and enhancing surfactivity, then drying in a vacuum environment, and then processing with nitrogen in a plasma processor, doping nitrogen elements to enhance the chemical properties of the electrode.

Benefits of technology

The prepared nitrogen-doped aluminum-nickel alloy electrode has high corrosion resistance and strong gas evolution properties, which significantly reduces the overpotential and improves the efficiency of hydrogen evolution and oxygen evolution reactions, and is suitable for alkaline seawater electrolysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753720A_ABST
    Figure CN119753720A_ABST
Patent Text Reader

Abstract

The invention discloses a nickel-based electrode with high corrosion resistance and strong gassing performance and a preparation method of the nickel-based electrode. The nickel-based electrode has relatively high safety, does not involve a high-temperature and high-pressure process, does not use an organic solvent, reduces environmental and operation risks, and ensures safety and reliability of a production process. Secondly, the method supports macro preparation, acid treatment can be carried out at room temperature, plasma treatment can be completed at low temperature, process conditions are mild, and the method is suitable for large-scale production and practical application. In addition, the method is simple and efficient in technological process, the used raw materials are easy to obtain, the equipment requirement is low, and the production cost is remarkably reduced. Due to the characteristic, the method has good economical efficiency and generalizability, and can meet the requirements of industrial preparation. The nitrogen-doped aluminum-nickel alloy coating nickel net prepared by the process not only has excellent electrochemical performance, but also shows good corrosion resistance and gassing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material surface treatment, and in particular relates to a nickel-based electrode with high corrosion resistance and strong gas evolution performance and a preparation method thereof. Background Art

[0002] Because hydrogen energy has the characteristics of high energy density and low pollution, it is considered to be an efficient and clean energy carrier for sustainable energy systems. Compared with acidic water electrolysis and neutral water electrolysis, alkaline water electrolysis has been widely studied due to its advantages such as lower corrosion and more cost-effective equipment. Because seawater is the most abundant water resource reserve on the earth, it has great potential for large-scale production of H2 and can also avoid increasing the use of fresh water, so the current development is mainly on seawater electrolysis to produce hydrogen. However, the main challenge of direct decomposition of natural seawater is the chlorine evolution reaction competing with the oxygen evolution reaction (OER), which not only reduces the durability of the catalyst due to corrosion, but also reduces the efficiency of decomposition of natural seawater. An effective way to solve the current problems in direct seawater electrolysis is to increase the pH value of seawater to alkaline (i.e., alkaline seawater electrolysis), and another way is to develop effective electrocatalysts. Although noble metal-based electrocatalysts exist as benchmark catalysts for hydrogen evolution reaction (HER) and OER in alkaline electrolytes, they cannot be widely used due to their high cost, scarce content and unstable performance.

[0003] Therefore, it is crucial to develop efficient, low-cost, non-precious metal electrocatalysts for alkaline seawater electrolysis. At present, most electrocatalysts used for alkaline seawater electrolysis are integrated self-supporting structure electrodes, in which most electroactive materials (such as Pt / Ni-Mo-NO, Pt-Co-Mo, Mo-CoPX / NF, CoFe@CoNi, etc.) are grown on three-dimensional substrates (such as nickel mesh, nickel foam, etc.). Nickel-based alloys are a class of electrocatalytic hydrogen evolution materials with excellent electrochemical properties. In recent years, people have actively developed nickel-based electrodes with high hydrogen evolution activity from the perspectives of energy factors and geometric factors, which has greatly developed nickel-based alloys. Among them, compared with other alloy materials, aluminum-nickel alloys are relatively mature in the industrial application of alkaline water electrolysis, but they still have a high overpotential in alkaline electrolytes and are less used in alkaline seawater electrolysis.

[0004] On the other hand, nickel mesh is listed as the first choice among many substrate materials due to its advantages such as good conductivity, low price and 3D network structure. Nickel mesh not only allows the active material to grow from bottom to top on its support, but also makes it easier for the electrolyte to penetrate. As a monolithic electrocatalyst, the catalytic activity of nickel mesh can be enhanced by different surface modification strategies. For example, T. Shahrabi et al. published an article titled Surface modification of Ni foam by the dendrite Ni-Cu electrode for hydrogen evolution reaction in an alkaline solution in the Journal of Electroanalytical Chemistry, proposing to synthesize Ni-Cu catalysts by optimizing the original nickel foam through dendrite coating to enhance HER activity. However, few studies have modified the alloy-coated nickel mesh into a monolithic electrode with resistance to chlorine corrosion and strong gas evolution to achieve a bifunctional integrated electrocatalyst for HER and OER in alkaline seawater. Therefore, in order to achieve efficient alkaline seawater electrolysis, it is key to modify the alloy catalyst and prepare a nickel-based electrode with high corrosion resistance and strong gas evolution.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide a nickel-based electrode with high corrosion resistance and strong gas evolution performance and a preparation method thereof, and solve the problems raised in the above-mentioned background technology.

[0007] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:

[0008] A method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance comprises the following steps:

[0009] Step A: using an aluminum-nickel alloy coated nickel mesh as a precursor material, placing it in an acid solution, soaking it at room temperature for 10-120 minutes, and then rinsing it with deionized water and ethanol to remove acid residues;

[0010] Step B: drying the rinsed nickel mesh in a vacuum environment, and obtaining an acid-treated aluminum-nickel alloy coated nickel mesh after drying;

[0011] Step C: placing the acid-treated aluminum-nickel alloy coated nickel mesh in a plasma treatment machine and performing plasma treatment under a vacuum environment, and obtaining a self-supporting nitrogen-doped aluminum-nickel alloy water electrolysis electrode after the plasma treatment.

[0012] Optionally, the number of times of rinsing with deionized water and ethanol in step A is 3-5 times.

[0013] Optionally, the acid solution in step A is one of sulfuric acid solution, hydrochloric acid solution or nitric acid solution, and the concentration of the acid solution is 0.01-2.0 mol / L.

[0014] Optionally, nitrogen gas needs to be introduced during the plasma treatment in step C, wherein the nitrogen gas flow rate is 50-200 ml / min and the treatment time is 0.1-2.0 hours.

[0015] Optionally, in step A, the nickel mesh is selected from any one of 20 mesh, 40 mesh, 46 mesh, 60 mesh, and 80 mesh.

[0016] Optionally, the alloy in the aluminum-nickel alloy coating in step A is Ni 1.1 Al 0.9 .

[0017] A nickel-based electrode with high corrosion resistance and strong gas evolution performance is prepared by the method for preparing the nickel-based electrode with high corrosion resistance and strong gas evolution performance.

[0018] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:

[0019] The present invention has high safety, does not involve high temperature and high pressure processes, and does not use organic solvents, which reduces environmental and operational risks and ensures the safety and reliability of the production process. Secondly, the method supports macro-scale preparation, acid treatment can be carried out at room temperature, and plasma treatment can be completed at low temperatures. The process conditions are mild and suitable for large-scale production and practical applications. In addition, the process flow of this method is simple and efficient, the raw materials used are easy to obtain, the equipment requirements are low, and the production cost is significantly reduced. This feature makes it have good economy and scalability, and can meet the needs of industrial preparation. The nitrogen-doped aluminum-nickel alloy coated nickel mesh prepared by this process not only has excellent electrochemical properties, but also exhibits good corrosion resistance and gas evolution properties.

[0020] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. In the drawings:

[0022] Figure 1 The characterization results of the nitrogen-doped aluminum-nickel alloy coated nickel mesh electrode prepared in Example 1 of the present invention; wherein, Figure 1 (a) is the XRD pattern; Figure 1 (b) is the SEM image; Figure 1 (c) is the element surface distribution diagram; Figure 1 (d) is the EDS diagram;

[0023] Figure 2 HER-LSV (a), OER-LSV (b) and total water splitting activity-LSV (c) curves of the nitrogen-doped aluminum-nickel alloy coated nickel mesh prepared in Example 1 of the present invention, the nitrogen-doped nickel mesh prepared in Comparative Examples 1, 2, and 3, the acid-washed aluminum-nickel alloy coated nickel mesh, and the un-acid-washed direct nitrogen-doped aluminum-nickel alloy coated nickel mesh;

[0024] Figure 3 The photos of bubbles precipitated from the nitrogen-doped aluminum-nickel alloy coated nickel mesh (a) and the non-nitrogen-doped aluminum-nickel alloy coated nickel mesh (b) during the electrolysis of water prepared in Example 1;

[0025] Figure 4 The SEM image (a) and element distribution diagram (b) of the aluminum-nickel alloy coated nickel mesh prepared in Example 2;

[0026] Figure 5 This is a SEM image of the nitrogen-doped aluminum-nickel alloy coated nickel mesh prepared in Example 4;

[0027] Figure 6 The SEM image, element surface distribution image and EDS image of the nitrogen-doped nickel mesh prepared in Comparative Example 1 are shown.

[0028] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0030] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0034] See also Figure 1-6 As shown, in this embodiment, a method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance is provided, comprising the following steps:

[0035] Step A: using an aluminum-nickel alloy coated nickel mesh as a precursor material, placing it in an acid solution, soaking it at room temperature for 10-120 minutes, and then rinsing it with deionized water and ethanol to remove acid residues;

[0036] Step B: drying the rinsed nickel mesh in a vacuum environment, and obtaining an acid-treated aluminum-nickel alloy coated nickel mesh after drying;

[0037] Step C: placing the acid-treated aluminum-nickel alloy coated nickel mesh in a plasma treatment machine and performing plasma treatment under a vacuum environment, and obtaining a self-supporting nitrogen-doped aluminum-nickel alloy water electrolysis electrode after the plasma treatment.

[0038] In this embodiment, the number of times of rinsing with deionized water and ethanol in step A is 3-5 times.

[0039] In this embodiment, the acid solution in step A is one of sulfuric acid solution, hydrochloric acid solution or nitric acid solution, and the concentration of the acid solution is 0.01-2.0 mol / L.

[0040] In this embodiment, nitrogen needs to be introduced during the plasma treatment in step C, wherein the nitrogen flow rate is 50-200 ml / min and the treatment time is 0.1-2.0 hours.

[0041] In this embodiment, the nickel mesh in step A is selected from any one of 20 mesh, 40 mesh, 46 mesh, 60 mesh, and 80 mesh.

[0042] In this embodiment, the alloy in the aluminum-nickel alloy coating in step A is Ni 1.1 Al 0.9 .

[0043] The present invention will now be further described in detail with reference to embodiments.

[0044] It should be noted that all raw materials in the examples of the present invention were obtained through commercial sources.

[0045] Embodiment 1: Provide a method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance, comprising the following steps:

[0046] Step A: Prepare a 0.5 mol / L hydrochloric acid solution as the acid treatment solution. -2 The aluminum-nickel alloy coated nickel mesh is immersed in the hydrochloric acid solution. It is left to soak for 30 minutes at room temperature to remove impurities on the surface of the nickel mesh and improve its surface activity. After the soaking is completed, it is rinsed three times with deionized water and ethanol respectively to ensure that the acidic substances remaining on the surface are completely removed. After rinsing, the nickel mesh is placed in a vacuum environment to dry to obtain the aluminum-nickel alloy coated nickel mesh after acid treatment.

[0047] Step B: Place the acid-treated nickel mesh in a plasma treatment machine for plasma treatment. During the treatment process, the treatment machine is evacuated and nitrogen is introduced with a flow rate controlled at 150 ml / min. The plasma treatment in a nitrogen environment lasts for 1 hour to ensure that the nitrogen element is evenly doped into the surface of the aluminum-nickel alloy coated nickel mesh to enhance the chemical properties and catalytic activity of the electrode.

[0048] Step C: After plasma treatment, a self-supporting nitrogen-doped aluminum-nickel alloy water electrolysis electrode is prepared.

[0049] The microstructure of the nitrogen-doped aluminum-nickel alloy coated nickel mesh prepared in this embodiment was characterized by SEM (scanning electron microscope) and XRD (X-ray diffraction) tests. Figure 1 As shown in the SEM image, nitrogen is uniformly doped on the surface of the nickel-based electrode, indicating that plasma treatment achieves uniform nitridation of the material surface. The aluminum-nickel alloy particles are evenly distributed on the nickel mesh matrix, forming an ideal three-dimensional structure, which helps to improve the rapid gas evolution and mass transfer efficiency during the electrolysis process.

[0050] from Figure 1In the XRD spectrum of (a), it can be observed that the peaks corresponding to the (111), (200) and (220) crystal planes of the nickel-based mesh appear at 44.507°, 51.846° and 76.37°, respectively, indicating that the crystal structure of the nickel mesh is preserved. At the same time, the diffraction peaks at 31.211°, 44.680°, 55.508°, 65.021° and 73.867° correspond to the Al 1.1 Ni 0.9 The (100), (110), (111), (200) and (210) crystal planes of the alloy indicate that the aluminum-nickel alloy grows uniformly in the electrode. It can be seen that the electrode maintains a good crystal structure and conductive properties after nitrogen doping.

[0051] In addition, through element surface distribution analysis Figure 1 (c), it can be clearly seen that Al, Ni and N elements are evenly distributed on the electrode surface. This shows that nitrogen is not only successfully doped into the aluminum-nickel alloy, but also evenly diffused throughout the nickel mesh structure. Further EDS (energy spectrum analysis) tests show that the nitrogen doping amount is 1.8wt%, indicating that the introduction of nitrogen has reached an ideal level, ensuring the corrosion resistance and catalytic performance of the material.

[0052] The HER (hydrogen evolution reaction) and OER (oxygen evolution reaction) performance tests conducted in a simulated seawater environment showed the excellent performance of the electrode. Figure 2 (a) shows that at 100 mA / cm 2 At a current density of 1.5 Å, the overpotential of the hydrogen evolution reaction of the nitrogen-doped electrode is 182 mV, which is significantly better than other comparative samples, such as nitrogen-doped nickel mesh (514 mV), acid-washed aluminum-nickel alloy coated nickel mesh (342 mV), and directly nitrogen-doped aluminum-nickel alloy coated nickel mesh without acid washing (283 mV). These results show that the synergistic effect of acid washing and nitrogen doping effectively reduces the overpotential and improves the efficiency of the hydrogen evolution reaction.

[0053] Similarly, in Figure 2 In the OER test shown in (b), the overpotential of the nitrogen-doped aluminum-nickel alloy coated nickel mesh is 180mV, which is much better than other comparative samples, such as nitrogen-doped nickel mesh (460mV), acid-washed aluminum-nickel alloy coated nickel mesh (320mV), and un-acid-washed nitrogen-doped aluminum-nickel alloy coating (230mV). These data prove that the electrode has excellent oxygen evolution reaction activity in an alkaline environment.

[0054] In addition, Figure 2 The full water electrolysis activity test in (c) shows that the electrode is 2The electrolysis potential at the current density of 1.50V was only 1.2V, which was much better than the performance of other samples, such as nitrogen-doped nickel mesh (2.2V), acid-washed aluminum-nickel alloy coated nickel mesh (1.83V), and un-acid-washed nitrogen-doped aluminum-nickel alloy coating (1.87V). This result shows the superiority of the prepared electrode in the overall water electrolysis reaction.

[0055] from Figure 3 The bubble precipitation photos in the figure can further verify the positive effect of nitrogen doping. In the process of water electrolysis, the nitrogen-doped nickel-based electrode ( Figure 3 (a)) and non-nitrogen-doped nickel mesh ( Figure 3 Compared with (b), the precipitated bubbles are smaller and denser, indicating that nitrogen doping not only improves the surface activity of the electrode but also optimizes the kinetics of gas evolution.

[0056] In summary, the nitrogen-doped aluminum-nickel alloy coated nickel mesh electrode prepared in this embodiment has significant corrosion resistance and excellent electrochemical properties, exhibits efficient hydrogen and oxygen evolution reaction activity in an alkaline environment, and is an ideal water electrolysis electrode material.

[0057] Embodiment 2: Provided is a method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance, comprising the following steps:

[0058] Step A: Prepare a 0.01 mol / L hydrochloric acid solution as the acid treatment solution. -2 The aluminum-nickel alloy coated nickel mesh is immersed in the hydrochloric acid solution. It is left to soak for 120 minutes at room temperature to remove impurities on the surface of the nickel mesh and improve its surface activity. After the soaking is completed, it is rinsed with deionized water and ethanol three times each to ensure that the acidic substances remaining on the surface are completely removed. After rinsing, the nickel mesh is placed in a vacuum environment to dry to obtain the aluminum-nickel alloy coated nickel mesh after acid treatment.

[0059] Step B: Place the acid-treated nickel mesh in a plasma treatment machine for plasma treatment. During the treatment process, the treatment machine is evacuated and nitrogen is introduced at a flow rate of 200 ml / min. The plasma treatment in a nitrogen environment lasts for 2 hours to ensure that the nitrogen element is evenly doped into the surface of the aluminum-nickel alloy coated nickel mesh to enhance the chemical properties and catalytic activity of the electrode.

[0060] Step C: After plasma treatment, a self-supporting nitrogen-doped aluminum-nickel alloy water electrolysis electrode is obtained.

[0061] The microstructure of the Nitrogen-doped Al-Ni alloy coated Ni mesh is shown in SEM images ( Figure 4The aluminum-nickel alloy particles on the surface of the nickel mesh remain intact and evenly distributed, indicating that the nitrogen doping process did not cause significant damage to the microstructure of the material. The aluminum-nickel alloy particles on the surface of the nickel mesh maintain an ideal crystalline state, which helps to maintain the electrical conductivity and structural stability of the electrode, ensuring its long-term durability during the electrolysis of water. In addition, this particle structure provides a good channel for the penetration of electrolytes and the rapid precipitation of gases, which is beneficial to improving the overall catalytic performance of the electrode.

[0062] The element surface distribution test results are as follows Figure 4 (b) shows the distribution of nitrogen, aluminum and nickel on the surface of the nickel mesh. From the element distribution diagram, it can be seen that although nitrogen doping was carried out, the distribution of nitrogen in the nickel mesh structure is not obvious enough, indicating that nitrogen has not been effectively incorporated into the surface of the material.

[0063] Embodiment 3: Provided is a method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance, comprising the following steps:

[0064] Step A: Prepare a 0.01 mol / L hydrochloric acid solution as the acid treatment solution. -2 The aluminum-nickel alloy coated nickel mesh is immersed in the hydrochloric acid solution. It is left to soak for 120 minutes at room temperature to remove impurities on the surface of the nickel mesh and improve its surface activity. After the soaking is completed, it is rinsed with deionized water and ethanol three times each to ensure that the acidic substances remaining on the surface are completely removed. After rinsing, the nickel mesh is placed in a vacuum environment to dry to obtain the aluminum-nickel alloy coated nickel mesh after acid treatment.

[0065] Step B: The acid-treated nickel mesh was placed in a plasma treatment machine for plasma treatment. During the treatment, the treatment machine was evacuated and nitrogen was introduced at a flow rate of 200 ml / min. The plasma treatment in the nitrogen environment lasted for 2 hours.

[0066] Step C: After plasma treatment, a self-supporting nitrogen-doped aluminum-nickel alloy water electrolysis electrode is obtained.

[0067] Embodiment 4: Provided is a method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance, comprising the following steps:

[0068] Step A: Prepare a 2 mol / L hydrochloric acid solution as the acid treatment solution. -2The aluminum-nickel alloy coated nickel mesh is immersed in the hydrochloric acid solution. It is left to soak for 30 minutes at room temperature to remove impurities on the surface of the nickel mesh and improve its surface activity. After the soaking is completed, it is rinsed three times with deionized water and ethanol respectively to ensure that the acidic substances remaining on the surface are completely removed. After rinsing, the nickel mesh is placed in a vacuum environment to dry to obtain the aluminum-nickel alloy coated nickel mesh after acid treatment.

[0069] Step B: The acid-treated nickel mesh was placed in a plasma treatment machine for plasma treatment. During the treatment, the treatment machine was evacuated and nitrogen was introduced at a flow rate of 150 ml / min. The plasma treatment in the nitrogen environment lasted for 0.5 hours.

[0070] Step C: After plasma treatment, a nickel-based electrode with damaged morphology is obtained.

[0071] SEM image of Nitrogen-doped Al-Ni alloy coated Ni mesh Figure 5 As shown, the microstructure after immersion in a high-concentration acid solution is shown. It can be clearly seen from the figure that the aluminum-nickel alloy particles are partially etched during the acid treatment, and the surface of the particles becomes rough and no longer uniform. The connection between local particles also breaks or collapses, indicating that the material has undergone significant chemical corrosion in a strong acid environment. This morphological damage may reduce the structural integrity of the electrode and affect its long-term stability.

[0072] In highly concentrated acid solutions, the aluminum element in aluminum-nickel alloys is more susceptible to corrosion and dissolution because aluminum has relatively poor corrosion resistance under acidic conditions. This etching action causes holes and depressions to appear on the surface of some particles, resulting in a reduction in the effective specific surface area of ​​the electrode. Although a certain degree of etching may help expose more active sites, excessive damage will weaken the mechanical strength of the nickel mesh and even cause structural failure of the electrode during the electrolytic reaction.

[0073] In addition, the damage caused by acid etching may also affect the electrochemical performance of the electrode. After acid immersion, the pore structure inside the material may be weakened, resulting in obstruction of the electrolyte penetration path, which will reduce the effective gas precipitation rate. At the same time, the irregular surface morphology may cause uneven local current distribution, which will reduce the efficiency of the electrocatalytic reaction of the electrode. Therefore, the acid concentration and immersion time need to be carefully controlled in the process to avoid excessive etching and ensure the integrity of the aluminum-nickel alloy particles and the stable performance of the electrode.

[0074] Embodiment 5: Provided is a method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance, comprising the following steps:

[0075] Step A: Prepare a 0.5 mol / L hydrochloric acid solution as the acid treatment solution. -2The aluminum-nickel alloy coated nickel mesh is immersed in the hydrochloric acid solution. It is left to soak for 120 minutes at room temperature to remove impurities on the surface of the nickel mesh and improve its surface activity. After the soaking is completed, it is rinsed with deionized water and ethanol three times each to ensure that the acidic substances remaining on the surface are completely removed. After rinsing, the nickel mesh is placed in a vacuum environment to dry to obtain the aluminum-nickel alloy coated nickel mesh after acid treatment.

[0076] Step B: Place the acid-treated nickel mesh in a plasma treatment machine for plasma treatment. During the treatment process, the treatment machine is evacuated and nitrogen is introduced with a flow rate controlled at 150 ml / min. The plasma treatment in a nitrogen environment lasts for 0.5 hours to ensure that the nitrogen element is evenly doped into the surface of the aluminum-nickel alloy coated nickel mesh to enhance the chemical properties and catalytic activity of the electrode.

[0077] Step C: After plasma treatment, a self-supporting nitrogen-doped aluminum-nickel alloy water electrolysis electrode is obtained.

[0078] Embodiment 6: Provided is a method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance, comprising the following steps:

[0079] Step A: Prepare a 0.5 mol / L hydrochloric acid solution as the acid treatment solution. -2 The aluminum-nickel alloy coated nickel mesh is immersed in the hydrochloric acid solution. It is left to soak for 120 minutes at room temperature to remove impurities on the surface of the nickel mesh and improve its surface activity. After the soaking is completed, it is rinsed with deionized water and ethanol three times each to ensure that the acidic substances remaining on the surface are completely removed. After rinsing, the nickel mesh is placed in a vacuum environment to dry to obtain the aluminum-nickel alloy coated nickel mesh after acid treatment.

[0080] Step B: Place the acid-treated nickel mesh in a plasma treatment machine for plasma treatment. During the treatment process, the treatment machine is evacuated and nitrogen is introduced at a flow rate of 200 ml / min. The plasma treatment in a nitrogen environment lasts for 2 hours to ensure that the nitrogen element is evenly doped into the surface of the aluminum-nickel alloy coated nickel mesh to enhance the chemical properties and catalytic activity of the electrode.

[0081] Step C: After plasma treatment, a self-supporting nitrogen-doped aluminum-nickel alloy water electrolysis electrode is obtained.

[0082] Embodiment 7: Provided is a method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance, comprising the following steps:

[0083] Step A: Prepare a 0.5 mol / L hydrochloric acid solution as the acid treatment solution. -2The aluminum-nickel alloy coated nickel mesh is immersed in the hydrochloric acid solution. It is left to soak for 30 minutes at room temperature to remove impurities on the surface of the nickel mesh and improve its surface activity. After the soaking is completed, it is rinsed three times with deionized water and ethanol respectively to ensure that the acidic substances remaining on the surface are completely removed. After rinsing, the nickel mesh is placed in a vacuum environment to dry to obtain the aluminum-nickel alloy coated nickel mesh after acid treatment.

[0084] Step B: Place the acid-treated nickel mesh in a plasma treatment machine for plasma treatment. During the treatment process, the treatment machine is evacuated and nitrogen is introduced with a flow rate controlled at 150 ml / min. The plasma treatment in a nitrogen environment lasts for 1.0 hour to ensure that the nitrogen element is evenly doped into the surface of the aluminum-nickel alloy coated nickel mesh to enhance the chemical properties and catalytic activity of the electrode.

[0085] Step C: After plasma treatment, a self-supporting nitrogen-doped aluminum-nickel alloy water electrolysis electrode is obtained.

[0086] Embodiment 8: Provided is a method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance, comprising the following steps:

[0087] Step A: Prepare a 0.5 mol / L hydrochloric acid solution as the acid treatment solution. -2 The aluminum-nickel alloy coated nickel mesh is immersed in the hydrochloric acid solution. It is left to soak for 30 minutes at room temperature to remove impurities on the surface of the nickel mesh and improve its surface activity. After the soaking is completed, it is rinsed three times with deionized water and ethanol respectively to ensure that the acidic substances remaining on the surface are completely removed. After rinsing, the nickel mesh is placed in a vacuum environment to dry to obtain the aluminum-nickel alloy coated nickel mesh after acid treatment.

[0088] Step B: Place the acid-treated nickel mesh in a plasma treatment machine for plasma treatment. During the treatment process, the treatment machine is evacuated and nitrogen is introduced with a flow rate controlled at 150 ml / min. The plasma treatment in a nitrogen environment lasts for 1.0 hour to ensure that the nitrogen element is evenly doped into the surface of the aluminum-nickel alloy coated nickel mesh to enhance the chemical properties and catalytic activity of the electrode.

[0089] Step C: After plasma treatment, a self-supporting nitrogen-doped aluminum-nickel alloy water electrolysis electrode is prepared, that is, a self-supporting nitrogen-doped aluminum-nickel alloy water electrolysis electrode is obtained.

[0090] Comparative Example 1: This comparative example provides a method for preparing a nitrogen-doped nickel mesh, comprising the following steps:

[0091] (1) Prepare a 0.5 mol / L hydrochloric acid solution;

[0092] (2) Commercially available 1*4cm -2The 46-mesh nickel mesh is immersed in the hydrochloric acid solution prepared in step 1, and after being immersed for 30 minutes, it is taken out and vacuum-dried to obtain a pretreated nickel-based electrode;

[0093] (3) The pretreated aluminum-nickel alloy coated nickel mesh was placed in a plasma treatment machine, evacuated and introduced with 150 ml / min of nitrogen, and plasma treated for 1.0 h to obtain a self-supporting nitrogen-doped aluminum-nickel alloy water electrolysis electrode.

[0094] SEM, element surface distribution, and EDS tests were performed on the nitrogen-doped nickel mesh, such as Figure 6 As shown in the figure, it can be seen that on the bare nickel mesh, in addition to the Al element, the N element is also evenly distributed in the selected area. In addition, EDS was performed on the nitrogen-doped aluminum-nickel alloy coated nickel mesh. It can be seen from the figure that the nitrogen content is 1.2wt%. The above tests prove the successful doping of nitrogen.

[0095] Comparative Example 2: This comparative example provides a method for preparing a pickled aluminum-nickel alloy coated nickel mesh, comprising the following steps:

[0096] (1) Prepare a 0.5 mol / L hydrochloric acid solution;

[0097] (2) The commercially available 1*4cm -2 The aluminum-nickel alloy coated nickel mesh is immersed in the hydrochloric acid solution prepared in step 1, and after being immersed for 30 minutes, it is taken out and vacuum-dried to obtain a pre-treated acid-washed nickel-based electrode;

[0098] Comparative Example 3: This comparative example provides a method for preparing a nitrogen-doped aluminum-nickel alloy coated nickel mesh, comprising the following steps:

[0099] A commercially available aluminum-nickel alloy coated nickel mesh was directly placed in a plasma treatment machine, evacuated, introduced with 150 ml / min of nitrogen, and plasma treated for 1.0 h to obtain a self-supporting nitrogen-doped aluminum-nickel alloy water electrolysis electrode.

[0100] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.

Claims

1. A method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance, characterized in that: The following steps are involved: Step A: using an aluminum-nickel alloy coated nickel mesh as a precursor material, placing it in an acid solution, soaking it at room temperature for 10-120 minutes, and then rinsing it with deionized water and ethanol to remove acid residues; Step B: drying the rinsed nickel mesh in a vacuum environment, and obtaining an acid-treated aluminum-nickel alloy coated nickel mesh after drying; Step C: placing the acid-treated aluminum-nickel alloy coated nickel mesh in a plasma treatment machine and performing plasma treatment under a vacuum environment, and obtaining a self-supporting nitrogen-doped aluminum-nickel alloy water electrolysis electrode after the plasma treatment.

2. The method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance according to claim 1, characterized in that: In step A, the number of times of rinsing with deionized water and ethanol is 3-5 times.

3. The method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance according to claim 1, characterized in that: The acid solution in step A is one of sulfuric acid solution, hydrochloric acid solution or nitric acid solution, and the concentration of the acid solution is 0.01-2.0 mol / L.

4. The method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance according to claim 1, characterized in that: In step C, nitrogen gas needs to be introduced during the plasma treatment, wherein the nitrogen gas flow rate is 50-200 ml / min and the treatment time is 0.1-2.0 hours.

5. The method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance according to claim 1, characterized in that: In step A, the nickel mesh is selected from any one of 20 mesh, 40 mesh, 46 mesh, 60 mesh and 80 mesh.

6. The method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance according to claim 1, characterized in that: The alloy in the aluminum-nickel alloy coating in step A is Ni 1.1 Al 0.9 .

7. A nickel-based electrode with high corrosion resistance and strong gas evolution performance prepared by the method for preparing a nickel-based electrode with high corrosion resistance and strong gas evolution performance as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Self-supporting phosphating nickel nanomaterial for hydrogen production with electrocatalytic decomposition of water and preparation method of self-supporting phosphating nickel nanomaterial

    CN106807416A